A STYLISTIC STUDY OF LIWANAG’S MOST LIKED ENGLISH SONGS OF BEN & BEN - Fajardo, Dan Fereth; Basilan, Michaela Marie; Bibonia, Rosa Mae; Braga, Glaidel Marie; Cabal, Jenny Rose; Ocampo, Ana; Purca, Kyla; Sentillas, Rizcel (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study examined Ben & Ben's most liked English songs. It aimed to know how the Theory of Foregrounding of Geoffrey Leech is employed. The songs are selected from Ben & Ben’s discography of hit singles based on the timeframes– 2017-2022. The present study qualitatively examined the selected songs using the theory of foregrounding, specifically, through the lens of linguistic deviations. Amongst the seven types of linguistic deviations, this paper includes a brief analysis of the linguistic deviation—lexical and semantic as they are the sole focus of this study. The linguistic deviations in expression and structure in the songs reflect intense emotions such as love, sadness, longing, pain, struggle, and frustration. The findings showed that there were several deviations under the lexical level in the selected Ben & Ben’s songs, there were affixation and compounding, while from the semantic point of view, the findings revealed that the songwriters used metaphor, oxymorons, hyperbole, and irony. The researchers concluded that the use of linguistic deviation has a complex impact on the songs’ meaning and message.